Transformation, theology and the public university in South Africa - R. Venter (Acta Theologica)
This article addresses a specific issue, namely the ramifications for theology practised at a public university under (post)-apartheid conditions. In South Africa, scholarly opinion has not paid sufficient attention to what “transformation” entails for theology under these circumstances. The article describes transformation in detail by clarifying the main referents for this notion and attending to discourses in higher education. Heuristic categories such as inclusivity, alterity, critique, freedom and flourishing are identified that should inform multi-level and comprehensive embodiment in terms of knowledge, people and practices. The article identifies several critical issues such as the plurality of intellectual traditions and identity formation that should be explored in more detail. It also emphasises the distinctive theological task of theology at a public university – the articulation of transcendence and the construal of a non-naturalistic symbolic interpretation of reality.